Conjugation morphology of Zygogonium ericetorum (Zygnematophyceae, Charophyta) from a high alpine habitat. Issue 1 (1st December 2015) - Stancheva, Rosalina; Herburger, Klaus; Sheath, Robert G.; Holzinger, Andreas
Abstract : Reproductive characteristics are important for defining taxonomic groups of filamentous Zygnematophyceae, but they have not been fully observed in the genus Zygogonium . Specimens of Z. ericetorum previously studied and used to clarify the generic concept lacked fertile material, which was obtained recently. This study illustrates for the first time, using color light microscopic and fluorescence images, a consequent conjugation stage in Z. ericetorum, including completely developed zygospores and purple cytoplasmic residue content left outside the zygospores, similar to aplanospore formation. Structures confirmed earlier reports and provided new observation informative regarding phylogenetically relevant reproductive characters of Z. ericetorum .